Optimizing the Critical Factors for Lipid Productivity during Stress Phased Heterotrophic Microalgae Cultivation - Chiranjeevi, P.; Venkata Mohan, S. (Frontiers in Energy Research, 2016)
Microalgae-derived biodiesel/biofuel is one of the promising and sustainable processes. In order to study the influence of different factors viz., pH, temperature, salinity and carbon concentration that influences the microalgae lipids and carbohydrate productivity Taguchi orthogonal array (OA) experimental design (DOE) was used with variation at four levels (21×44). Experiments were performed with allegorical batch experimental matrix [16 experimental trails]. Salinity, temperature, carbon concentration and pH showed marked influence on lipid production whereas temperature and carbon concentration showed major influence on carbohydrate production. Higher lipid productivity (55%) was observed with experimental condition six (pH: 6; Salinity: 1 g/l; Temperature: 20 OC; Carbon concentration: 30 g/l). FAME analysis revealed the highest number of Saturated fatty acids (SFAs) (C12:0 to C24:0) was detected with experimental set up six and eight more favoring the biodiesel properties.